"Læge i tyske koncentrationslejre". Lejrfortællingen i den kollektive erindring af Anden Verdenskrig i Danmark - Iversen, Stefan (Passage - Tidsskrift for litteratur og kritik, 2011)
Stefan Iversen: “Doctor in German Concentration Camps. Camp Narratives in the Collective Memory of Second World War in Denmark” Based on a reading of narrative structures in Paul Thygesen’s testimony Læge i tyske koncentrationslejre [Doctor in German Concentration Camps] the article discusses the roles played by Danish narratives from German concentration camps in the Danish collective memory of the Second World War. The article’s main argument is that while Denmark during the last decade deliberately has joined a transnational memory of Holocaust, this transnational commemoration runs the risk of further accelerating an already apparent eradication of the memory of Danish camp narratives; narratives that due to the special circumstances of the deportations from Denmark call for specific approaches in order not to be forgotten.